Prevalence of Post-Surgical Maxillary Defects and Causes of Maxillary Resections in Patients Presenting at Tertiary Care Hospitals of Multan, Pakistan - Rida Anjum; Maria Komil Ghumman; Malik Adeel Anwar; Waleed Ishaq; Sana Urooj; Umar Farooq (Pakistan Journal of Medicine and Dentistry)
Background: Maxillectomy, often necessitated by late-stage malignancies, results in significant anatomical and functional impairments profoundly affecting the quality of life of the affected patients. This study aimed to assess the prevalence of maxillary post-surgical defects and, primary causes of maxillectomy among patients in South Punjab, Pakistan.